Malkawi, Fathi. “Bias in Western Educational Thought,” Year 10, Issues 37-38 (Summer-Fall 1425 AH/ 2004 CE), Pp. 181-202. - ملكاوي, فتحي (Al-Fikr al-islāmī al-muʿāṣir (previously Islamiyat al-Ma'rifah), 2004)
Fathi Malkawi’s article presents aspects of bias in Western educational thought and explains how these aspects constitute serious obstacles in the way of educational reform in the Muslim world, given that most reform efforts derive their concepts, theories, and models from the West. He presents this without calling for an intellectual disconnect with the West in the area of educational reform. The article discusses the term “bias” and its indicants, the nature of Western educational thought, how politics and media reinforce bias, and the epistemological and methodological sources of bias in Western educational thought. It then discusses the concept of secularism and its impact on bias in Western educational thought, concluding that an intellectual disconnect with Western intellectual should not take place.